If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x(-1)-3=0.4x(-1)-2
We move all terms to the left:
4x(-1)-3-(0.4x(-1)-2)=0
We multiply parentheses
-4x-(0.4x(-1)-2)-3=0
We calculate terms in parentheses: -(0.4x(-1)-2), so:We get rid of parentheses
0.4x(-1)-2
We multiply parentheses
0x-2
We add all the numbers together, and all the variables
x-2
Back to the equation:
-(x-2)
-4x-x+2-3=0
We add all the numbers together, and all the variables
-5x-1=0
We move all terms containing x to the left, all other terms to the right
-5x=1
x=1/-5
x=-1/5
| u2-12-7u=0 | | -(5+2)-7=-4x-(x+9) | | 6x^2-24x+40=0 | | u/4=74 | | 5/4n-7/6=5/24 | | j/36=3 | | -3x-9=-5x+19 | | .2=m−2.5 | | 5x-11=x | | 50-x=70.2 | | 50-x=70×2 | | -5(-2x+8)+4x=-40+14x | | -7=67-2d | | 2(5n+3)=86 | | 3x-7=(x-1)+7 | | x-62=128 | | x+5/6=17/12 | | 7x-4=142 | | 3x+3=4+x+-1 | | 4x-6=48-5x | | -2(-32+6s)=30-s | | 7x2+10x=-3 | | 4/7=12x | | 133+6x+5=180 | | 3/4h-9=1/4h- | | 5(1+1x)=40 | | 2x=30-8 | | 6d−2/11=2d−213 | | 3(5x+10)=135 | | 0.17x+x=4000 | | 8g+6(g-2)=-10(g-4)2g | | 5=1–2u |